Valoración agronómica y fitosanitaria de 106 accesiones de avena (Avena sativa), trigo (Triticum aestivum) y cebada (Hordeum vulgare) en la localidad de Naguan provincia Bolívar - Heredia Guerrero, Diana Geraldine (2022)
This research is entitled "Agronomic and phytosanitary assessment of 106 accessions of oats (avena sativa), wheat (Triticum aestivum) and barley (Hordeum vulgare) in the town of Naguan Bolívar Province, owned by the UEB. The objectives set forth in this study were: to determine the agronomic and phytosanitary characteristics of 106 accessions of oats, wheat and barley in the area. Select the best lines of oats, wheat and barley. Develop a research database of oats, wheat and barley. The factors under study were: 52 accessions of oats; 39 Wheat accessions and 15 Barley accessions, where each line was considered as a treatment; for the evaluation of the variables, descriptive statistics were used such as; frequency, percentages, averages, maximums and minimums. The main conclusions obtained were: the highest average of oats with respect to yield per plant was obtained by A10 and A17 with 75 and 83 grains in their order. For the incidence of rust in oats (P. coronata), 32 of the accessions registered resistance and/or absence of the disease. The evaluated wheat accessions presented the highest average with respect to the yield per plant in B38 with 67 grains and the average yield potential for this locality was 38 grains. For the incidence of leaf rust (P.striiformis), only 10.3% of wheat accessions registered susceptibility to the disease. The highest average with respect to yield per plant in barley was obtained by C15 with 35 grains. There was an average of 20 grains/plant for this locality. For the incidence of rust in barley (P.striiformis) and (P. hordei) only one line was susceptible. Finally, 30 oat accessions were selected; 21 wheat and 11 barley